2016
DOI: 10.3389/fpsyg.2016.01756
|View full text |Cite
|
Sign up to set email alerts
|

Social Brain Hypothesis: Vocal and Gesture Networks of Wild Chimpanzees

Abstract: A key driver of brain evolution in primates and humans is the cognitive demands arising from managing social relationships. In primates, grooming plays a key role in maintaining these relationships, but the time that can be devoted to grooming is inherently limited. Communication may act as an additional, more time-efficient bonding mechanism to grooming, but how patterns of communication are related to patterns of sociality is still poorly understood. We used social network analysis to examine the association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(61 citation statements)
references
References 85 publications
3
58
0
Order By: Relevance
“…In contrast shorter duration of time spent in proximity would be associated with higher 150 rate of response absence and response by communication. Roberts and Roberts 2016b). We therefore predict that 156 the centrality of individual chimpanzees will be associated with the rate of singe, rapid and control for these biological factors in all models.…”
Section: Introduction 25mentioning
confidence: 89%
“…In contrast shorter duration of time spent in proximity would be associated with higher 150 rate of response absence and response by communication. Roberts and Roberts 2016b). We therefore predict that 156 the centrality of individual chimpanzees will be associated with the rate of singe, rapid and control for these biological factors in all models.…”
Section: Introduction 25mentioning
confidence: 89%
“…266 Next, to ensure that the sampling procedure did not bias our results, we examined 267 whether there was a similarity in association patterns between scans taken at 2 (scan 1), 4 268 (scan 2) and 18 minutes (scan 9) interval of the focal sample including both sexes. These 269 analyses showed that there was no significant difference in the number of times focal and 270 non-focal subjects were in close proximity within the samples but there was a difference 271 between the samples [Roberts and Roberts, 2016b]. The behavioural measures were then 272 derived and the method can be summarized by the following equations: 2002; Roberts and Roberts, 2016a;Roberts and Roberts, 2017;Roberts and Roberts, 2018a; community of chimpanzees have been previously determined and we used this information to 299 classify the dyads as maternally related or not [Reynolds, 2005].…”
mentioning
confidence: 99%
“…Chimpanzees live in fission-fusion communities within which they associate temporarily in 108 subgroups ('parties') that vary in size, composition and duration [Goodall, 1986]. Individuals 109 in the community are often spatially and temporarily separated but nonetheless recognise 110 each other and maintain long-term relationships [Foerster et al, 2015; Langergraber et al, 111 2009; Mitani, 2009; Mitani et al, 2002;Roberts and Roberts, 2016b]. Maintaining the 112 differentiated set of social relationships that arises from this fission-fusion structure is 113 hypothesised to be a key driver of communicative complexity [Freeberg et al, 2012; Roberts 114 and Roberts, 2016b].…”
mentioning
confidence: 99%
See 2 more Smart Citations